NEW NORMAL APPROPRIATE LEARNING MODEL: 2NAL MODEL DURING CIVID-19 PANDEMIC FOR UNDERGRADUATES OF THAI EDUCATIONAL INSTITUTIONS - Thamasan Suwanroj , Orawan Saeung (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Due to the serious COVID-19 pandemic and the adjustment of educational management in Thailand that caused the change of learning model from old to new normal by online learning at home, the objectives of this research were to study and analyze the factors of new normal appropriate learning model: 2NAL model during CIVID-19 pandemic for undergraduates of Thai educational institutions. The method of study was divided into 2 phases. First phase was to study the factors of new normal appropriate learning model for undergraduates discussed by 9 experts of public educational institutions. In-depth interview was used to ask the opinions about the factors of new normal appropriate learning model for Thai undergraduates. The questions were clearly structured and used for individual interview. For this phase, the data were analyzed by using qualitative data analysis. The second phase was to analyze the factors of new normal appropriate learning model for undergraduates discussed by 1,126 experts of all public educational institutions which provide undergraduate degree across Thailand. The research instrument was the questionnaire used to ask the opinions about the factors of new normal appropriate learning model for undergraduates. The data were analyzed by using confirmatory factor analysis for this phase. New knowledge gained from the research was new normal appropriate learning model: 2NAL model which consisted of the factors as follows: 1) Content Literacy 2) Intelligence Literacy 3) Digital Literacy 4) Self Literacy5) Collaborative Literacy and 6) Curiosity Literacy. The results were very useful and important in developing new normal appropriate learning model during CIVID-19 pandemic for undergraduates of Thai educational institutions in the next phase of the research. Also, it was used for learning management in the digital age with practical application.